PENGGUNAAN KARTU KATA DALAM LATIHAN KETERAMPILAN MENULIS BAHASA MANDARIN DI SMP LKIA PONTIANAK - Nurfitria, Asyifa; Ina, Ina; Lusi, Lusi (Universitas Tanjungpura, 2023)
Chinese characters play a very important role in Chinese language teaching. Mastering Chinese characters can improve students' ability to write them. To create a good learning process, teachers can use exciting teaching methods, such as using Chinese character cards to train students to write Chinese characters. Chinese character cards are a foreign language teaching method, which is a method of teaching language through the coordination of speech and movement. This study applies Chinese character cards to improve students' ability to write Chinese characters. The subjects of the study were second-grade students in LKIA middle school. The results of the study showed that the students' ability to write Chinese characters improved after applying for the Chinese character cards. The average score on the pre-test was 56% and the average score on the post-test after the experiment was 81%. This shows that the students' mastery of the stroke order of Chinese characters increased by 25%, which proving that the use of Chinese characters cards can improve the students' ability to write Chinese characters.